Effect of chronic administration and withdrawal of caffeine on motor function, cognitive functions, anxiety, and the social behavior of BLC57 mice - Mahdi, Sadiq; Almosawi, Sayed; Baksh, Hasan; Qareeballa, Abdulrahman; Alsaleh, Bano; Falamarzi, Faisal; Alrabaani, Malak; Alkalbani, Ali; Kamal, Amer (International Journal of Health Sciences, 2019)
Objectives: The cognitive functions, motor coordination, and social behavior were studied in rodents after adding different doses of caffeine in their drinking water. Methodology: BLC57 mice were divided into four groups: Control (n = 8), chronic moderate dose (n = 8, Ch] MD), Ch high dose (n = 8, Ch HD), and withdrawal (n = 8, WD). Caffeine was administered for 1 month to all groups. Spatial memory was tested by Morris water maze, motor coordination by rotarod (RR), social behavior by (Crawley’s test), and anxiety by elevated plus maze (EPM) test. Results: In water maze, the latency to reach the platform was significantly shorter in Ch MD group compared to the control and the Ch HD groups. WD group showed the worst performance. RR results showed that the groups treated with caffeine performed poor in comparison to the control group where their latency to fall was significantly less. In the three-chamber test, the Ch MD group showed enhanced sociability (session 1) and social novelty behavior (session 2). On the other hand, both Ch HD and WD showed a lack in sociability and a deficit in social novelty. In the EPM, results showed that all caffeine administrated mice where more anxious than the control group. Conclusion: We concluded that chronic administration of caffeine in MD resulted in enhancement of spatial memory, motor functions, sociability, and social novelty. The anxiety in these animals was, however, increased. On the other hand, Ch HD caffeine had opposite effects on all the parameters except for anxiety.